Comparing fiber quality characteristics and staple length in Suri and Huacaya alpacas - Pinares, Rubén; Meza, Aydee; Crispín, Neyla; Lozano, Franklin; Pezo, Danilo (Frontiers in Animal Science, 2023)
Introduction The textile industry considers alpaca fiber to be a specialty fiber. The aim of this study was to evaluate the influence of color, breed, location, age, and sex of alpacas on fiber quality characteristics and staple length. Methods Fiber samples were taken from the mid-side of 118 Huacaya and Suri alpacas at two livestock shows (Pitumarca and Maranganí) and at CICAS La Raya (South American Camelid Research Center), which is located in the province of Canchis (Cusco, Peru). Results and discussion The fiber characteristics and staple length in black alpacas are similar to those of brown alpacas. Huacaya fiber is finer, having a lower mean fiber diameter (MFD), SD, and coefficient of variation of MFD than Suri fiber. Alpacas from the two livestock shows have higher-quality fiber than unselected alpacas raised in CICAS La Raya. Staple length is longer in Suri alpacas than in Huacaya alpacas. Likewise, the staple length is longer in alpacas from Pitumarca, followed by alpacas from Maranganí, and is shorter in alpacas from CICAS La Raya. Young alpacas have a shorter staple length than adults, and it is longer in females than in males. The mean fiber diameter and spinning fineness are strongly correlated with other fiber characteristics in colored alpacas. Conclusion These black and brown alpacas raised in small herds and judged in two livestock shows produce high-quality fiber at 22 µm for the textile industry.